NUTM1 Gene Fusions Characterize a Subset of Undifferentiated Soft Tissue and Visceral Tumors. (May 2018) - Dickson, Brendan C.; Sung, Yun-Shao; Rosenblum, Marc K.; Reuter, Victor E.; Harb, Mohammed; Wunder, Jay S.; Swanson, David; Antonescu, Cristina R.
Abstract : NUT midline carcinoma is an aggressive tumor that occurs mainly in the head and neck and, less frequently, the mediastinum and lung. Following identification of an index case of a NUTM1 fusion positive undifferentiated soft tissue tumor, we interrogated additional cases of primary undifferentiated soft tissue and visceral tumors for NUTM1 abnormalities. Targeted next-generation sequencing was performed on RNA extracted from formalin-fixed paraffin-embedded tissue, and results validated by fluorescence in situ hybridization using custom bacterial artificial chromosome probes. Six patients were identified: mean age of 42 years (range, 3 to 71 y); equal sex distribution; and, tumors involved the extremity soft tissues (N=2), kidney (N=2), stomach, and brain. On systemic work-up at presentation all patients lacked a distant primary tumor. Morphologically, the tumors were heterogenous, with undifferentiated round-epithelioid-rhabdoid cells arranged in solid sheets, nests, and cords. Mitotic activity was generally brisk. Four cases expressed pancytokeratin, but in only 2 cases was this diffuse. Next-generation sequencing demonstrated the following fusions: BRD4-NUTM1 (3 cases), BRD3-NUTM1, MXD1-NUTM1, and BCORL1-NUTM1 . Independent testing by fluorescence in situ hybridization confirmed the presence of NUTM1 and partner gene rearrangement. This study establishes that NUT-associated tumors transgress the midline and account for a subset of primitive neoplasms occurring in soft tissue and viscera. Tumors harboring NUTM1 gene fusions are presumably underrecognized, and the extent to which they account for undifferentiated mesenchymal, neuroendocrine, and/or epithelial neoplasms is unclear. Moreover, the relationship, if any, between NUT-associated tumors in soft tissue and/or viscera, and conventional NUT carcinoma, remains to be elucidated. Abstract : Supplemental Digital Content is available in the text.